British women of the Eastern Front : war, writing and experience in Serbia and Russia, 1914-20 - Smith, Angela K. (Manchester University Press, 2016)
This book explores the experiences and contributions of British women performing active service across the Eastern Front in Serbia, Russia and Romania during the First World War, focusing on representation of that experience though a range of written records.